Modelling Reactive and Proactive Behaviour in Simulation: A Case Study in a University Organisation - Mazlina, Abdul Majid; Herawan, Tutut (SERSC, 2013)

(untitled)
This paper compares two well-known simulation techniques to model human reactive and different level of details for proactive behaviour modelling in service systems. The simulation methods used are Discrete Event Simulation (DES) and combined DES and Agent-Based Simulation (ABS) called DES-ABS. We consider two proactive human behaviours which are taking charge from experience and taking the initiative to fulfil a goal. We investigate the similarities and differences of model results performance in both simulation models. The results of our experiments show that the level of pro-activeness considered in the simulation model has a big impact on the output. However, there is no significant difference between the results from the DES and the DES-ABS simulation models. Therefore, for service systems of the type we investigated, it is suggested to use DES as the preferred analysis tool.